Pengaruh Intensitas Cahaya Terhadap Produksi Umbi Tanaman Lobak (Raphanus Sativus L) - Parman, Sarjana (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2010)
Research of effect of light intensity towrd on Raphanus sativus tuber has be done, beginning at 1 August 2009-15 Decenber 2009 in paddy fields Popongan Salatiga. This research used design randomized complete block design, one treatment is given light intensity as low light intencity with one piece plastick strimin, two pieces strimin as medium light intencity, and high intencity without strimin plastick as controls. Every treatment was reapeating 5 times. Analysis data used komputer programs SPSS-13. Result this showed that given defferent light intensity on plant caused defferent on long and wet and dry tuber formation in first harvesting The second harvesting that 60 day age plant caesed defferently on total folium, wide and west and dry folium.